Clinical and radiological outcomes of lumbar endoscopic decompression for treating lumbar spinal stenosis and degenerative lumbar scoliosis: a retrospective study at mean 4.4 years follow-up - Fan, Ning; Wang, Aobo; Yuan, Shuo; Du, Peng; Wang, Tianyi; Zang, Lei (Frontiers in Surgery, 2025)
PurposeTo assess the clinical and radiological outcomes of lumbar endoscopic decompression for the treatment of lumbar spinal stenosis (LSS) with concurrent degenerative lumbar scoliosis (DLS).MethodsThis study retrospectively reviewed 97 patients with LSS and DLS who underwent lumbar endoscopic decompression between 2016 and 2021. The average follow-up duration was 52.9 months. Another 97 LSS patients without DLS were selected as the control group. The pre- and postoperative visual analog score (VAS) and the Oswestry disability index (ODI) were recorded and analyzed to compare clinical outcomes. Radiological findings, such as coronal balance and intervertebral disc height, have also been reported.ResultsBoth groups' mean VAS scores for back pain, leg pain, and ODI were significantly improved two weeks after surgery and at the final follow-up (p < 0.001). There was no significant difference in the prevalence of surgical complications or patient satisfaction rates. However, patients in the DLS group reported more severe back pain at the final follow-up than those in the LSS group (p = 0.039). Radiological follow-up revealed no significant deterioration in coronal imbalance or loss of disc height in either group.ConclusionLumbar endoscopic decompression can be a safe and effective surgical technique for treating LSS with DLS, particularly in elderly patients with poor general conditions.